Enzymatic extraction of pectin from artichoke (Cynara scolymus L.) by-products using Celluclast®1.5L. (15th June 2018) - Sabater, Carlos; Corzo, Nieves; Olano, Agustín; Montilla, Antonia
Graphical abstract: Highlights: Artichoke by-products have been characterised and are an alternative source of pectin. Pectin extraction from artichoke by-products using Celluclast®1.5L has been optimised. The yield of pectin extraction was 20.3% of artichoke by-product. Extracted pectin was low methoxyled with a degree of esterification of 19.5. Artichoke pectin contained 69.5% of galacturonic acid and 12.2% of arabinose. Abstract: The aim of this study was to optimise pectin extraction from artichoke by-products with Celluclast®1.5L using an experimental design analysed by response-surface methodology (RSM). The variables optimised were artichoke by-product powder concentration (2–7%, X1 ), enzyme dose (2.2–13.3 U g −1, X2 ) and extraction time (6–24 h, X3 ). The variables studied were galacturonic acid (GalA) (R 2 93.9) and pectic neutral sugars (R 2 92.8) content and pectin yield (R 2 88.6). In the optimum extraction conditions (X1 = 6.5%; X2 = 10.1 U g −1 ; X3 = 27.2 h), pectin yield was 176 mgg −1 dry matter (DM). Considering 27.2 h of treatment as the +α value given by the design, the extraction time was increased up to 48 h obtaining a yield of 221 mg g −1 DM. The enzymatic method optimised allows obtaining artichoke pectin with good yield, high GalA (720 mg g −1 DM) and arabinose (127.6mgg −1 DM) contents and degree of methylation of 19.5%.